Comparative phenology of dormant Japanese pear (Pyrus pyrifolia) flower buds: a possible cause of 'flowering disorder'. (23rd January 2018) - Ito, A; Sakaue, T; Fujimaru, O; Iwatani, A; Ikeda, T; Sakamoto, D; Sugiura, T; Moriguchi, T
Abstract: Mild winters influenced by global warming have increased the incidence of erratic flowering ('flowering disorder') in Japanese pear ( Pyrus pyrifolia Nakai) trees in Japan. To discover how, when and what kind of disorder/damage occur in pear flower buds, we observed axillary flower buds of two cultivars, 'Kosui' (a mid-chill cultivar) and 'Niitaka' (a high-chill cultivar), grown at five locations. We focused on the phenology from autumn 2015 to spring 2016, when temperatures were higher than for average years, especially from September to January, and large fluctuations occurred due to El Niño. During the blooming season in the spring of 2016, both the percentage of blooming flower buds and the number of florets per flower bud decreased in trees located at lower latitudes (with lower chilling accumulation) with a more severe problem in 'Niitaka' than in 'Kosui'. As shown by forcing excised shoots, the onset and release of endodormancy occurred earlier in 'Kosui' than 'Niitaka' and occurred earlier in trees growing at higher latitudes than at lower latitudes (warmer regions). The freezing tolerance of flower buds, measured as the lethal temperature for 50% survival (LT50 ), was similar for the cultivars beginning in autumn and reached maximum levels, LT50 values of less than −12 °C, between late-December and mid-January in both cultivars, except for those in Kagoshima (the lowest latitude), where the maximum LT50 was only −5 °C throughout the season. We propose that warmer autumn–winter temperatures may prevent the acquisition of freezing tolerance, disturb endodormancy progression and disrupt floral organ development, thereby causing flowering disorder in pear trees. The risk of occurrence of flowering disorder in pear may be higher in high-chill cultivars than in low- or mid-chill cultivars and at lower latitudes compared with higher latitudes.